The Influence of Occupational Stress on Work Productivity with Social Support as a Moderating Variable: A Case Study of Spx Express Luragung Hub - Devi Yuliana; Agi Syarif Hidayat (Greenation International Journal of Economics and Accounting, 2026)
This research aims to analyze the effect of work stress on work productivity with social support as a moderating variable for SPX Express Luragung Hub employees. The dynamic and high-pressure logistics work environment has the potential to give rise to work stress which results in decreased productivity. The research used a quantitative approach with a survey method of 83 respondents using saturated sampling techniques. Analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The research results show that work stress has a negative and significant effect on work productivity (β = -0.296; p < 0.05). Social support was proven to significantly moderate this relationship (β = 0.208; p < 0.05), thereby weakening the negative impact of work stress. These findings emphasize the importance of managing work stress and strengthening social support in maintaining the productivity of logistics sector employees.